Panov's theorem for weak Hopf algebras - Christian Lomp (2019)
Panov proved necessary and sufficient conditions to extend the Hopf algebra structure of an algebra R to an Ore extension R[x; sigma, delta] with x being a skew-primitive element. In this paper we extend Panov's result to Ore extensions over weak Hopf algebras. As an application we study Ore extensions of connected groupoid algebras.